Megjegyzések a Szerb Vajdaság történeti problémájához - Marjanucz, László (Közép-Európai Közlemények, 2011)
The Serbs arrived in Hungary in masses, while fleeing from the Turkish, at the end of 17th century. Their status was ruled by imperial privileges and not by the Hungarian laws. This condition also contributed to the fact, that the Serbs started to relate their originally ecclesiastical franchise to the South-Hungarian areas where they lived, to turn their ecclesiastical autonomy into secular autonomy. The estates –considering it as an illegitimate effort –dismissed it from the beginning, but the Habsburgs approached to it tactically. When in 1848 the civilian Hungarian nation and Vienna had a conflict, the latter supported the idea of creating a separate Serbian territory. Thus the dream of the Serbs who lived in Hungary was fulfilled: the territorially separated Serbian Vojvodina. However, it proves the tactical contribution of Vienna, that in the separated area actual practice of power was not possible for the Serbs. It couldn’t be, because Vojvodina didn’t have a Serbian nature, the majority of the people were Hungarians, Romanians and Germans, while the Serbs didn’t make even the ¼ of it. But even Vienna itself thought, that instead of the national separation, a nationally mixed area would lead to political balance. Therefore, in the regional authorities qualified and trustworthy czech-german officers practised the power. In the Bach period the the idea of the Serbian Vojvodina seemed to be a dead end, that was also accepted by Miltics Szvezotár, but he trusted in the resurrection of its new form.